A Rare Complication of Stapled Hemorrhoidopexy: Giant Pelvic Hematoma Treated with Super-Selective Percutaneous Angioembolization - Francesco Ferrara (Shiraz University of Medical Sciences, 2018)
Introduction: Procedure for prolapsed hemorrhoids (PPH) or hemorrhoidopexy is not free from complications, some of whichhave been described as serious, such as bleeding. This study describes a case of a female patient with post-operative huge pelvichematoma, successfully treated with percutaneous angioembolization.Case Presentation: A 76-year-old female underwent PPH, with no intraoperative complications. Few hours later, the patient showedsigns of acute abdomen. No external rectal bleeding was identified and vital signs were normal. A computerized tomography (CT)-scan showed a giant peri-rectal and retroperitoneal pelvic hematoma, with signs of active bleeding. A subsequent selective arteriographyshowed huge bleeding from superior hemorrhoidal artery, treated with super-selective embolization. The procedure wassuccessful and the patient showed a symptomatic improvement. The subsequent hospital stay was uneventful and she was dischargedon the ninth post-operative day, with no complications. At the 30-day post-discharge follow-up, the patient was completelypain free with no signs of pelvic discomfort. Control CT scan revealed regression of the pelvic hematoma.Conclusions: Severe complications may occur after PPH and one of the most important is local bleeding. In the current case, nosigns of external active bleeding were noted. Prompt diagnosis with CT scan allowed efficacious non-operative treatment with angioembolization,avoiding the need of reoperation for a potential serious complication.